The religious function of the psyche - Corbett, Lionel (London ; New York : Routledge, 1996)
The Religious Function of the Psyche offers an examination of divinity that focuses on its unique, personal manifestations within the psyche, the body, relationships and the world at large. Using the language and interpretive methods of depth psychology, particularly those of C. G. Jung and psychoanalytic self psychology, the author, Lionel Corbett, offers an introduction to Jung and religion and a bridge between the transpersonal and the personal levels of the psyche. Lionel Corbett suggests a psychological model for the relationship between the divine and the human, and offers an alternative approach to spirituality than that found in traditional religious systems. Problems of evil, suffering, and the notion of human development as an incarnation of spirit, are dealt with in this book by a religious approach to the psyche that can be applied in both everyday life and within the practice of psychotherapy.
1. The Religious Attitude in Psychotherapy -- 2. Personal Spirituality Based on Contact with the Numinosum -- 3. The Transpersonal Self: A psychological approach to the divine -- 4. The Archetype as Synthetic Principle: Making psychology and spirituality synonymous -- 5. Mythical, Symbolic and Imaginal Aspects of the Psyche's Religious Function -- 6. A Psychological View of Some Traditional Religious Ideas -- 7. A Depth Psychological Approach to the Problem of Suffering -- 8. Suffering: The search for meaning -- 9. Sin and Evil: A psychological approach -- 10. Psychotherapy and Spiritual Practice -- 11. The Rationale for a Contemplative Psychology.
Includes bibliographical references (p. 246-251) and index.
Description based on print version record.
Keywords: Psychology, Religious; Jungian psychology -- Religious aspects; Religieus bewustzijn; Psychologie religieuse; Psychologie analytique -- Aspect religieux; Jung, Carl G; Religionspsychologie; Tiefenpsychologie; RELIGION / Psychology of Religion; Electronic books